2022
DOI: 10.3390/cancers14235959
|View full text |Cite
|
Sign up to set email alerts
|

Digital Quantification of Intratumoral CD8+ T-Cells Predicts Relapse and Unfavorable Outcome in Uveal Melanoma

Abstract: Although it is a disease that occurs mainly in the Caucasian population, uveal melanoma (UM) is the most common primary intraocular tumor in adults. Here, we used digital pathology and image analysis for the diagnosis of UM and the prediction of the prognosis. Our retrospective study included a total of 404 histopathological slides from 101 patients. A digital image acquisition and quantitative analysis of tissue immune biomarkers (CD4, CD8, CD68, CD163) were performed. A negative impact of the intratumoral CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Jiang et al reported that PD-1 expression on uveal melanoma cells induced tumor proliferation and predicted poor survival in UVM patients 28 . Recent research suggests that the speci c distribution characteristics of CD8 T cells in UVM can potentially predict the risk of relapse and death, providing guidance for drug therapy selection 10 . Notably, the combination of nivolumab and ipilimumab has demonstrated activity in metastatic uveal melanoma with a high and sustained drug response, as shown by Meredith S Pelster et al 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al reported that PD-1 expression on uveal melanoma cells induced tumor proliferation and predicted poor survival in UVM patients 28 . Recent research suggests that the speci c distribution characteristics of CD8 T cells in UVM can potentially predict the risk of relapse and death, providing guidance for drug therapy selection 10 . Notably, the combination of nivolumab and ipilimumab has demonstrated activity in metastatic uveal melanoma with a high and sustained drug response, as shown by Meredith S Pelster et al 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that the immune microenvironment plays a pivotal role in the progression and metastasis of various cancers, including uveal melanoma (UVM). Several investigations have demonstrated a positive correlation between heightened in ltration of macrophages and CD8 + T cells in UVM and an increased risk of metastasis and unfavorable prognosis 10 . However, immunotherapy has shown limited effectiveness in UVM, highlighting the need to explore multiple targets for treatment.…”
Section: Introductionmentioning
confidence: 99%